The impact of Portuguese legislative changes in local accommodation - Almeida, Paula (2020)
This study seeks to fill the epistemological gap regarding the impact of legislative and regulatory means of managing local accommodation, has been changed, as it relates to the cultural identity of cities and parts of cities in Portugal. We presume such a cultural identity to be a complex entity which is built in part in negotiation with the tourist, but one that is currently being done on an imbalanced relationship. This study is conducted from a law studies point of view, seeking to draw conclusions from recent touristic trends especially in the cities of Porto and Lisbon. The Governmental Decree nº128/2014, August 29th, with the news brought by Decree nº63/2015 created severe dangers to municipal institutions: the risk of ‘desertification’ of the center by local citizens, rent pressure, social polarization, amongst other risks, which led to the “gentrification phenomenon” that has occurred in other centers such as Barcelona, Venice and Berlin. This growth has been leveraged by the use of digital platforms that promote accommodation, like Airbnb, Homeway and Booking. While these digital platforms relate to a shared economy and the democracy of tourism phenomenon as it allows tourists to find accommodation adjusted to their budgets, the lack of policing also led to some scams and taxes evasion. In order to control the unbridled growth of local accommodation in some areas, the national legislator has imposed in Law nº62/2018, 22 of august, the possibility to municipalities to establish, by regulation, some containment areas, to contain registration of more places as local accommodation. On the course of this study we propose to approach the impact of this solution and evaluate the economic impact of these legal efforts to contain that growth.